LEGAL FOUNDATIONS OF LEGAL CLINICS' ACTIVITIES IN THE REPUBLIC OF ARMENIA - Markosyan, Tigran; Paronyan, Nare (Bulletin of Yerevan University C: Jurisprudence, 2026)
Legal clinics traditionally fulfill two main missions-educational and social- serving as a unique model of legal education and of legal aid provision. At the same time, it is evident that the effectiveness of legal clinics' activities is largely conditioned by the presence of necessary and sufficient functional, structural, procedural, and material prerequisites. Moreover, in order to grant these prerequisites an institutional character, it is essential to provide them with appropriate legal regulation.Based on theoretical sources, Armenian legislation, and both international and domestic practices, this article presents the role and significance of legal clinics, explores the content of the concept of a “legal clinic,” analyses their educational and social functions, and discusses the essential preconditions for their effective operation.A separate subject of discussion has been the insufficient level of legislation regulating the activities of legal clinics, including limitations on students involved in legal clinics to carry out court representation, the absence of effective tools for obtaining evidence necessary for legal assistance, the lack of requirements ensuring client confidence in the clinic, such as professional conduct rules for the clinic, and others.In the article, the authors present a number of scientific-practical conclusions that can serve as guidelines for improving the effectiveness of legal clinics' activities and further development of the clinical education system.
Keywords: legal clinic; clinical legal education; educational program; educational institution; free legal aid; socially vulnerable groups; public defense; court representation; supplementary mechanism; code of conduct